2017
DOI: 10.1038/srep41087
|View full text |Cite
|
Sign up to set email alerts
|

Comparative molecular dynamics studies of heterozygous open reading frames of DNA polymerase eta (η) in pathogenic yeast Candida albicans

Abstract: Genomic instability in Candida albicans is believed to play a crucial role in fungal pathogenesis. DNA polymerases contribute significantly to stability of any genome. Although Candida Genome database predicts presence of S. cerevisiae DNA polymerase orthologs; functional and structural characterizations of Candida DNA polymerases are still unexplored. DNA polymerase eta (Polη) is unique as it promotes efficient bypass of cyclobutane pyrimidine dimers. Interestingly, C. albicans is heterozygous in carrying two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…It suggested that the amino-terminal catalytic domain of CaPolη is not involved in PCNA interaction. Since CaPolη functionally complements ScPolη and protects the fungal cells from UV-induced DNA damages ( 17 , 25 , 26 ), to further strengthen our finding, various Polη orfs were expressed under the constitutive ADH1 promoter in rad30Δ and rad30Δrev3Δ S. cerevisiae strains, and susceptibility to UV irradiation was determined. Polη and Polζ (Rev3-Rev7) function in the error-free and error-prone branches of TLS of UV lesions, respectively; therefore, double deletant S. cerevisiae ( rad30Δrev3Δ ) strain becomes hypersensitive to UV radiation than the individual null strain ( 31 ).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…It suggested that the amino-terminal catalytic domain of CaPolη is not involved in PCNA interaction. Since CaPolη functionally complements ScPolη and protects the fungal cells from UV-induced DNA damages ( 17 , 25 , 26 ), to further strengthen our finding, various Polη orfs were expressed under the constitutive ADH1 promoter in rad30Δ and rad30Δrev3Δ S. cerevisiae strains, and susceptibility to UV irradiation was determined. Polη and Polζ (Rev3-Rev7) function in the error-free and error-prone branches of TLS of UV lesions, respectively; therefore, double deletant S. cerevisiae ( rad30Δrev3Δ ) strain becomes hypersensitive to UV radiation than the individual null strain ( 31 ).…”
Section: Resultssupporting
confidence: 67%
“…The S. cerevisiae RAD30 homolog from the pathogenic yeast C. albicans has been characterized. The complementation analysis suggested that CaPolη suppresses UV sensitivity and UV-induced mutagenesis in a Polη-deficient S. cerevisiae strain ( 25 , 26 , 27 , 28 ). By mutational analyses, we confirmed the absence of pip motif in CaPolη and provided the first conclusive evidence to suggest an indispensable role of the ubz domain of Polη in TLS function, which is also well supported by Polη from S .…”
mentioning
confidence: 99%
“…Our earlier and current structural modeling and complementation analyses in various S. cerevisiae rad30Δ strains suggested that both the alleles CaRAD30A and CaRAD30B are structural and functional homologs of the cognate Saccharomyces gene (Satpati et al, 2017). Hence, this gene should be considered as RAD30 instead of RAD32 as mentioned in Candida Genome Database.…”
Section: Discussionmentioning
confidence: 98%
“…As C. albicans exhibits considerable genotypic variation both in vitro and in clinical isolates due to genetic alterations (Ahmad et al, ; Ciudad, Hickman, Bellido, Berman, & Larriba, ; Rustchenko, ), DNA polymerases (Pol) could play a crucial role in fungal pathogenesis. Recently, we have characterized C. albicans Polη (Rad30), a Y‐family DNA polymerase, which promotes efficient bypass of ultraviolet (UV)‐induced cyclobutane pyrimidine dimers and cisplatin adducts (Acharya et al, ; Manohar, Peroumal, & Acharya, ; Satpati, Manohar, Acharya, & Dixit, ). In our earlier study, we showed that the roles of CaPolη in genome stability, genotoxins‐induced filamentation, and azole drug tolerance are due to its translesion DNA synthesis (TLS) activities, whereas its TLS‐independent functions play a pivotal role in serum‐induced morphogenesis and amphotericin B resistance.…”
Section: Introductionmentioning
confidence: 99%
“…albicans Polη (Rad30), a Y-family DNA polymerase, which promotes efficient bypass of ultraviolet (UV)-induced cyclobutane pyrimidine dimers and cisplatin adducts Satpati, Manohar, Acharya, & Dixit, 2017). In our earlier study, we showed that the roles of CaPolη in genome stability, genotoxins-induced filamentation, and azole drug tolerance are due to its translesion DNA synthesis (TLS) activities, whereas its TLS-independent functions play a pivotal role in seruminduced morphogenesis and amphotericin B resistance.…”
mentioning
confidence: 99%